2016
DOI: 10.1016/j.jid.2016.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA PICSAR Promotes Growth of Cutaneous Squamous Cell Carcinoma by Regulating ERK1/2 Activity

Abstract: Keratinocyte-derived cutaneous squamous cell carcinoma (cSCC) is the most common metastatic skin cancer, and its incidence is increasing globally. Long noncoding RNAs (lncRNA) are involved in various biological processes, and their role in cancer progression is emerging. Whole transcriptome analysis of cSCC cells (n = 8) and normal human epidermal keratinocytes (n = 4) revealed overexpression of long intergenic ncRNA (LINC00162) in cSCC cells. The expression of LINC00162 in cSCC cells was upregulated by inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
78
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 47 publications
4
78
0
Order By: Relevance
“…The functions of PICSAR (p38 inhibited cutaneous squamous cell carcinoma associated lncRNA) in breast cancer have not been reported. However, studies have shown that PICSAR promotes the growth of cutaneous squamous cell carcinoma by activating the ERK1/2 signal pathway [47]. Similar to PICSAR, some miRNAs were detected in the present study, which have rarely been studied in the field of breast cancer study, but have been shown to play important roles in other fields.…”
Section: Discussionsupporting
confidence: 72%
“…The functions of PICSAR (p38 inhibited cutaneous squamous cell carcinoma associated lncRNA) in breast cancer have not been reported. However, studies have shown that PICSAR promotes the growth of cutaneous squamous cell carcinoma by activating the ERK1/2 signal pathway [47]. Similar to PICSAR, some miRNAs were detected in the present study, which have rarely been studied in the field of breast cancer study, but have been shown to play important roles in other fields.…”
Section: Discussionsupporting
confidence: 72%
“…This is perhaps not altogether surprising in light of abundant evidence that lncRNAs, defined as noncoding genomic transcripts greater than 200 nucleotides in length, play central roles in regulating a diverse array of biological processes in both normal development and pathogenesis (Wang and Chang, 2011). The recent work by Piipponen et al (2016) shows the importance of understanding the regulatory role of lncRNAs in cSCCs and underscores the potential usefulness of lncRNAs as both prognostic biomarkers and therapeutic targets.…”
mentioning
confidence: 99%
“…Although this emphasizes how critical the regulatory roles of lncRNAs can be, it also strongly suggests a key role for lncRNAs in the cellular disarray leading to cancer. Because investigations into such ideas have only just begun, the mechanistic insights and innovative investigative approaches put forth by Piipponen et al (2016) will undoubtedly be of particular importance to the skin cancer field moving forward.…”
mentioning
confidence: 99%
“…LINC00162 is upregulated by the inhibition of the p38α and p38δ mitogen-activated protein kinases. Knockdown of LINC00162 inhibited proliferation and migration of SCC cells in vitro and inhibited extracellular signal-regulated kinase 1/2 activity, up regulating dual specificity phosphatase 6 (DUSP6) [17]. Other, recently published molecules involved in the complex biology of SCC are Ets2 and Elk3 genes, required for malignant progression from AK lesions to SCC.…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%